PELAKSANAAN TUGAS DAN WEWENANG DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN KUNINGAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) - Ahmad Noor Kholis Majid , Indarja, Ratna Herawati (Diponegoro Law Journal, 2013)
Regional autonomy is defined as the effort to empower regions and the people to  improve the people’s welfare in all life aspects including in tourism field. Therefore, tourism sector become one of regional potencies developed by all regional governments, particularly Kuningan District, to support the development of  people’s  welfare  through  increasing   Regional  Original  Revenue  (PAD). Regional Original Revenue (PAD) is the source of regional income obtained from its own region collected based on regional regulation in accordance  with the applicable law (Article 1 of the Act No. 33, 2004). Then, Regional Original Revenue is the original source of original income coming from regional potencies. Regional  Government  can  explore  the  sources  of  Regional  Original  Revenue optimally.The method  applied  in  this  research  was  normative  juridical  research meaning that  anything written in laws or regulations is made into a concept as principle/ norm, and used as  the standard for appropriate human behavior. The aim of this research is to recognize whether  the implementation of duties and authorities of the Tourism and Culture Agency of Kuningan District, West Java, has been in accordance with the law or not.The research results show that the implementation of duties and authorities of the Tourism and Culture Agency of Kuningan District, West Java, has been regulated in the  Regulation of Kuningan Regent No. 42, 2008 on the Main Duties, Functions, and Job Description of the Tourism and Culture Agency of  Kuningan  District  from  the  side  of  product  and  attraction,  facilities  and infrastructure,  market  and  promotion,  and  human  resources.  To  find  out  the problems,  several  efforts  have  been  performed  by  the  Tourism  and  Culture Agency of Kuningan District by applying the Regional Regulation No. 7, 2009 on the  Master Plan of Regional Tourism Development (RIPPDA). RIPPDA is the formulation  of  the   major  policies  on  the  planning  and  using  of  tourism development  in  the  region  including  the  aspects  of  spatial  planning,  tourism business,   supporting                       factors,         and      continuous                  tourism         development    with environmental conception for optimizing tourism potencies in harmony, balance, integrated, well-arranged, and preserved.